CRYSTALLIZATION ENVIRONMENT OF KAZAKHSTAN MICRODIAMOND: EVIDENCE FROM NANOMETRIC INCLUSIONS AND MINERAL ASSOCIATIONS - Dobrzhinetskaya L.F.; Green H.W.; Bozhilov K.N.; Mitchell T.E.; Dickerson R.M. (My University, 2003)
Nanometric solid inclusions in diamond incorporated in garnet and zircon from felsic gneiss of the Kokchetav massif, Kazakhstan, have been examined utilizing electron microscopy and focused ion beam techniques. Host garnet and zircon contain numerous pockets of multiple inclusions, which consist of 1–3 diamond crystals intergrown with quartz, phengite, phlogopite, albite, K-feldspar, rutile, apatite, titanite, biotite, chlorite and graphite in various combinations. Recalculation of the average chemical composition of the entrapped fluid represented by multiple inclusion pockets indicates that such fluid contained a low wt% of SiO2, suggesting a relatively low-temperature fluid rather than a melt. Transmission electron microscopy revealed that the diamond contains abundant nanocrystalline inclusions of oxides, rare carbonates and silicates. Within the 15 diamond crystals studied, abundant inclusions were found of SiO2, TiO2, FexOy, Cr2O3, ZrSiO4, and single grains of ThxOy, BaSO4, MgCO3, FeCr2O4 and a stoichiometric Fe-rich pyroxene. The diversity of trace elements within inclusions of essentially the same stoichiometry suggests that the Kokchetav diamond crystallized from a fluid containing variable amounts of Si, Fe, Ti, Cr, Zr, Ba, Mg and Th and other minor components such as K, Na, P, S, Pb, Zn, Nb, Al, Ca, Cl. Most of the components in crystals included in diamond appear to have their origin in the subducted metasediments, but some of them probably originate from the mantle. It is concluded that Kokchetav diamond most likely crystallized from a COH-rich multicomponent supercritical fluid at a relatively low temperature (hence the apparently low content of rock-forming elements), and that the diversity of major and minor components suggests interactions between subducted metasediments and mantle components.
Keywords: COH-fluid; Kazakhstan microdiamond; nanoinclusions; oxides; subduction